Retrograde branched extension limb assembling stent of pararenal abdominal aortic aneurysm: A longitudinal hemodynamic analysis for stent graft migration. (14th September 2020) - Mei, Yuqian; Xu, Huanming; Ma, Wei; Li, Zhenfeng; Yang, Rui; Yuan, Hai; Peng, Yan; Wu, Muyang; Chen, Zhangtao; Guo, Wei; Gao, Tianxin; Xiong, Jiang; et al.
Abstract: Purpose: Pararenal abdominal aortic aneurysms (PRAAAs) are a life‐threatening disease, and hemodynamic analysis may provide greater insight into the effectiveness and long‐term outcomes of endovascular aneurysm repair (EVAR). However, the lack of patient‐specific boundary conditions on the periphery compromises the accuracy. Windkessel (WK) boundary conditions coupled to hemodynamic follow‐up models of a PRAAA patient, aims to provide insights into the link between hemodynamics and poor prognosis. Method: One PRAAA patient underwent EVAR and reintervention after one branch of stent‐graft (SG) had migrated. Totally five computational follow‐up models were studied. Patient‐specific flow data acquired via ultrasound were used to define the boundary conditions in the ascending aorta and the following three branches. Coupled zero‐dimensional WK models representing the distal vasculature were used to define the outlet boundary conditions under the abdomen. Results: Flow divisions of the main SG branches were 40.7% and 24.7%, respectively. Time‐averaged wall shear stress and oscillatory shear index (OSI) increased at the junction connected the SG branch and the stent leading to the right common iliac artery (RCIA) where the stent migrated. The OSI and relative residence time (RRT) value in superior mesenteric artery increased notably after the migration, the RRT continuously increased following the reintervention. Conclusion: Unbalanced flow, resulting in locally high‐speed flow, high WSS and OSI might significantly affect stent stability. Results suggest that diameters and interconnection design of stents in complex cases should take the flow division into consideration and computational simulations might be considered as a tool for intervention protocol design. Abstract : Results indicate the unbalance flow division and high angulation configuration could be the principal reasons for stent migration with the support of high TAWSS, OSI distribution at the migration site. For further application, this study suggests that the diameter design of bifurcated SG should consider the flow division and the number of leading branches. And clinicians should be more careful when deposing a stent graft to an artery with high angulation.